Cutaneous lava migrans in the paediatric foot. (6th December 2010) - Griksaitis, Michael; Pennock, Victoria; Nair, Asha
Abstract : Dermatological referrals to paediatrics are a common occurrence often with a vast range of diagnoses made prior to referral to secondary care services. The authors report a case of cutaneous lava migrans infection in an 11-year-old girl in Northern England following her return from a family holiday in Jamaica. The authors report this case to raise awareness of this diagnosis. This girl initially received treatment for alternate diagnoses, and our aim is to encourage people to think of tropical dermatoses as a diagnosis in the returning traveller of all age groups.